Optimal coding for bit-rate limited networked control systems in the presence of data loss - Silva, E.I.; Quevedo, D.E.; Goodwin, G.C. (2007 46th IEEE Conference on Decision and Control, 2007)
This paper studies networked control of SISO LTI plant models, where the communication channel is subject to both quantization and data dropouts. Using a standard signal-to-noise ratio constrained white noise model for quantization, we derive coder-decoder pairs that minimize the impact of channel artifacts on closed loop performance. In addition, we provide a simple necessary and sufficient condition that guarantees the stability of the considered networked control system architecture.